PERAN GURU PPKn DALAM MEMBANGUN KARAKTER TANGGUNG JAWAB DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA SMP NEGERI 3 ROKAN IV KOTO - Sinulingga, Rizki Handayani; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research was to know the effect of teacher,s civics role in building responsibility character to students result in study civics in SMP Negeri 3 Rokan IV Koto. The populations and the simples of this research were 79 studens. This research used sampling jenuh teachique. The techniques of collecting the data used in this research were observation, share the questionnaire, inerview adn document. Here ,the researcher uses Regression Linier analysis as the data analysis technique. The result of this research showed that there is no effect of teachers civics role in building character to students result in study civics in SMP Negeri 3 Rokan IV Koto. Meanwhile, it showed by the experiment of Regression Linier beween Variable X and Variable Y, the result Of Fhitung was 2,482 and the value of F tabel was, 3,97 that from the distribution teble of Fhitung and N= 79, with significant level 5% thus, Fhitung ˂ F tabel or 2,482 ˂ 3,97 it means that HO diterima and HA ditolak, in additional there is no effect between teachers role in building responsibility character to students result in study civics in SMP Negeri 3 Rokan IV Koto. In this case, it is better for techer to improve their role, especially as mediator, facilitator and the students should force themselves to improve their comprehension.Key Words : teachers role, responsibility character, studen result